2004
DOI: 10.1161/01.hyp.0000127914.94292.76
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Enhances Endothelial Apoptosis via Upregulation of Fas-Mediated Pathways

Abstract: Abstract-Hyperhomocysteinemia is an independent risk factor for the development of atherosclerosis. However, the underlying mechanism of endothelial cell injury in hyperhomocysteinemia has not been elucidated. In this study, we examined the effect of homocysteine (Hcy)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 59 publications
1
67
0
Order By: Relevance
“…Potential mechanisms whereby homocysteine might contribute to atherosclerosis include endothelial injury due to release of reactive oxygen species by oxidized homocysteine, increased oxidation of lowdensity lipoprotein, and stimulation of smooth muscle cell proliferation (31). Homocysteine enhances endothelial cell apoptosis (32). It is interesting to note that patients with SLE have increased levels of circulating apoptotic endothelial cells and reduced brachial artery flow-mediated dilation (33), and yet, despite accelerated damage, they have decreased numbers of circulating endothelial cell precursors, cells that are essential for vascular repair (34).…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms whereby homocysteine might contribute to atherosclerosis include endothelial injury due to release of reactive oxygen species by oxidized homocysteine, increased oxidation of lowdensity lipoprotein, and stimulation of smooth muscle cell proliferation (31). Homocysteine enhances endothelial cell apoptosis (32). It is interesting to note that patients with SLE have increased levels of circulating apoptotic endothelial cells and reduced brachial artery flow-mediated dilation (33), and yet, despite accelerated damage, they have decreased numbers of circulating endothelial cell precursors, cells that are essential for vascular repair (34).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of Hcy are independent risk factor for cardiovascular diseases [Keaney et al, 1993;Suhara et al, 2004]. Because endothelial cells are lacking the cystathione beta synthase [Finkelstein, 1990[Finkelstein, , 1998], an enzyme responsible for Hcy clearance; endothelial cells are the prime target for Hcy toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…PARP; cytochrome-c; reactive oxygen species; siRNA; cardiac microvascular endothelial cells; oxidative stress; mitochondrial membrane potential; siRNA; cDNA array; TUNEL; Bax; Bcl 2 ; caspase Hyperhomocysteinemia is an independent risk factor for cardiovascular disease, stroke, and peripheral vascular disease [Jacobsen, 1998;Hankey and Eikelboom, 1999;Fallon et al, 2001;Suhara et al, 2004] [Tsai et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…Increased HC levels have also been detected in obese diabetic patients (Sanchez-Margalet et al 2002). HC exerts detrimental effects on a number of cell lineages including endothelial cells (Blundell et al 1996) and neuronal cells (Kim & Pae 1996), at least partially mediated through production of reactive oxygen species (ROS; Skurk & Walsh 2004), which induce DNA damage and apoptosis (Suhara et al 2004). Studies using insulin-secreting BRIN-BD11 pancreatic beta cells demonstrated that both acute and prolonged exposure to HC had detrimental effects on beta cell glucose metabolism, insulin secretory responsiveness and cell viability (Patterson et al 2006a(Patterson et al ,b, 2007a.…”
Section: Introductionmentioning
confidence: 99%